2018
DOI: 10.1140/epjc/s10052-018-6125-1
|View full text |Cite
|
Sign up to set email alerts
|

Higgs alignment from extended supersymmetry

Abstract: We consider the effective type-II two-Higgs doublet model originating from Dirac gaugino models with extended supersymmetry in the gauge sector, which is automatically aligned in the simplest realisations. We show that raising the scale at which the extended supersymmetry is manifest and including quantum corrections actually improves the alignment. Using an effective field theory approach including new threshold corrections and two-loop RGEs, plus two-loop corrections to the Higgs mass in the low-energy theor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 96 publications
2
58
0
Order By: Relevance
“…An N = 2 SUSY in turn leads automatically to alignment [12] due to the SU (2) R-symmetry of the two Higgs doublets (which form an N = 2 hypermultiplet) [13]. This alignment is surprisingly robust under quantum corrections, where there is an accidental cancellation of N = 2 breaking effects [12]. Moreover, it has been found that the R-symmetry also prevents chiralityflip diagrams, which significantly relaxes flavour constraints [14][15][16] and suppresses squark production at the LHC, rendering DG models "supersafe" [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…An N = 2 SUSY in turn leads automatically to alignment [12] due to the SU (2) R-symmetry of the two Higgs doublets (which form an N = 2 hypermultiplet) [13]. This alignment is surprisingly robust under quantum corrections, where there is an accidental cancellation of N = 2 breaking effects [12]. Moreover, it has been found that the R-symmetry also prevents chiralityflip diagrams, which significantly relaxes flavour constraints [14][15][16] and suppresses squark production at the LHC, rendering DG models "supersafe" [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…These results also allow us to understand why the simple identification of couplings in the Higgs couplings with their N = 2 expected values, as it was attempted for the MRSSM in [3], fails to achieve alignment. There, the integration out of the additional doublets breaks the SU (2) R R-symmetry explicitly at tree level.…”
Section: R-symmetric Higgs Alignmentmentioning
confidence: 89%
“…as given in [4,6]. Again, restricting to the case of CP conserving Lagrangian, the two CP even scalars have squared-mass matrix (2.10) with…”
Section: A Model With Su (2) R Symmetrymentioning
confidence: 99%
“…Such an alignment without decoupling [1] was realized in [2] ( see the discussion of the spectrum in Section 3 of [2], the model was not engineered for this purpose but as a scenario for supersymmetry breaking, and therefore we can consider the alignment there as a "prediction" of the model) and discussed later in [3,4]. In particular, it was shown in [4] that the alignment survives with an impressive precision when radiative corrections are taken into account. The mechanisms behind this successful alignment are a combination of a global SU (2) R symmetry of the quartic potential and diverse cancellations due to supersymmetry as discussed in [5] and will be reviewed here.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation